Circular migration and language skills in german: a multilingual self-learning portfolio for live-in carers - Middeke, Annegret (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
So-called 24-hour carers, also known as live-in carers, support people in need of care in private households. In Germany, they are mainly women from Eastern Europe. Under the conditions of circular migration, most of them find themselves not only in a legal grey area, but also in a transnational rift characterised by a lack of social participation. A multilingual workplace-related self-learning portfolio (“Carer Qualification in German”) for live-in carers from Eastern Europe is intended to improve their professional situation and strengthen their self-empowerment. The materials are adapted to the individual living and working conditions and also include cooperative forms of learning in order to involve the person being cared for and their social environment in the learning process.